Mathematical methods for sample surveys - Tucker, Howard G. (Singapore ; River Edge, N.J. : World Scientific, 1998)
This book is about both the mathematics of sample surveys and about sample surveys. The mathematics is both elementary and rigorous. A sizeable part of the book covers the discrete probability needed for the sampling methods covered. Topics then covered are: simple random sampling, sampling with unequal probabilities, linear relationships, stratified sampling, cluster sampling and two-stage sampling.
Includes index.
oif 05/02/15
Loan
Keywords: Sampling (Statistics); Mathematical statistics